Advanced analysis of blade work - Kleshnev, V. (BioRow, 2018)
In a previous Newsletter, we found that the blade normal velocity in the water became negative (i.e. the blade centre is moving toward its rear surface) just after the catch and just before the finish. This all happens while the blade is producing some propulsive force, so blade efficiency was calculated higher than 100% at these phases. Here we try to explain this paradox.